Strong turbulent flow in the subauroral region in the Antarctic can deteriorate satellite-based navigation signals - D. S. Kotova; A. A. Sinevich; A. A. Chernyshov; D. V. Chugunin; Y. Jin; W. J. Miloch (Scientific Reports)
Abstract In the subauroral zone at the boundary of the auroral oval in the evening and night hours during geomagnetic disturbances, a narrow (about 1°–2°) and extended structure (several hours in longitude) is formed. It is known as a polarization jet (PJ) or the subauroral ion drift (SAID). The PJ/SAID is a fast westward ion drift and is one of the main signatures of a geomagnetic disturbance in the subauroral ionosphere at the altitudes of the F-layer, when the geomagnetic AE index reaches more than 500 nT. Plasma speed in the PJ/SAID can reach several kilometres per second, and the size of plasma irregularities inside it can reach scales from tens of meters to several hundred meters. Such high velocities and structured plasma can affect trans-ionospheric radio waves and lead to scintillations in the received signal. We show that at the moment of auroral activity intensification, an increase in the magnitude of phase scintillation index (σϕ) as well as loss of satellite signals lock were observed in the region of the PJ/SAID equatorward of the auroral oval over Dronning Maud Land (Queen Maud Land) in Antarctica. We find that fluctuations inside the PJ/SAID can lead to serious deterioration of radio communication or navigational services. We emphasize the importance of considering the geometry of the beam passing from the GNSS satellite to the receiver on the ground. We highlight the mutual contribution of the PJ/SAID and the diffuse aurora boundary, which are almost impossible to separate in practice. Our results demonstrate the importance of considering the subauroral zone, where very dynamic plasma formations can occur with a strong flow and various-scale irregularities inside that lead to serious interference in satellite communications.